Penerapan Metode Hand-on (drill) dan Bimbingan Konseling bagi Siswa Slow Learner Di SMU Negeri 2 Ambon - Sipahelut, Junita; Tuhumury, Jamie Lee (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2023)
Slow learners are students who are slow learners and need more time than other groups of students. In general, these students have quite poor grades for all subjects because they have difficulty in capturing lessons. Therefore, appropriate methods and counseling are needed for teachers who will teach slow learner students. The purpose of this study is the extent to which the application of hand on (drill) subject teachers and counseling for class teachers, parents and Slow Learner students can change the behavior of lack of confidence and learning outcomes in Chemistry and Physics subjects. This research uses a descriptive qualitative approach. The data collection techniques used were observation, interviews, IQ tests and documentation. Data analysis techniques use data reduction and data presentation. The results showed that the application of the hand on (drill) method in chemistry and physics subjects could be carried out optimally and there was an increase in understanding as well as tasks and Slow Learner student scores were quite good from before. The application of counseling for class teachers, parents and slow learner students has good results, this can be seen from slow learner students who have begun to interact with classmates, and have begun to depend less on their mothers. Keywords: Hand On Drill Method, Counseling, Slow Learner